Pengembangan Produk Pariwisata Melalui Penerapan Prinsip-Prinsip Ekowisata Bahari Di Pantai Labuhan Amuk, Desa Antiga, Karangasem, Bali - Nazhima, Adilah Ata; Arida, I Nyoman Sukma (JURNAL DESTINASI PARIWISATA, 2019)
Background in this research begins with the existence of two kinds of tourism that is mass tourism and Alternative tourism, where in Alternative tourism there is one kind of tourism that is Ecotourism. Marine Tourism is one form of ecotourism. Labuan Amuk Beach has great natural potential to be developed. Lots of activities that can be done at Labuan Amuk Beach such as snorkeling and fishing. The purpose of this research is to know the existing condition of Labuan Amuk Beach, to develop product activity through its own natural potential, to identify product development opportunities, and to describe marine eco-tourism principles in Labuan Amuk Beach. Data collection in this research is done by observation, interview, and documentation. The method used in this research is qualitative method and the collected data is analyzed descriptively qualitative. The result obtained in this research is the existing condition of Labuan Amuk Beach which consists of attraction, accessbilites, amenities, and anciliary. While the potential is in Labuan Amuk Beach is the potential of nature and get what are the opportunities of product development and know the explanation of the principles of marine ecotourism at Labuan Amuk Beach Some suggestions that should be considered in this research are improvements to the role of government as facilitators and local communities as participants. In addition, the need for cooperation between stakeholders to synergize with each other to develop tourism in Labuan Amuk Beach . Keyword : Development, Potential, Product, Marine Ecotourism